Analysis of Basic and Non-Basic Sectors on Export Commodity Opportunities with Location Quontent, Shift Share and Klassen Typology Approaches in Aceh Province - Fajar Daniel Samosir; Reni Ria Armayani Hasibuan; Aqwa Naser Daulay (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to analyze and determine the basic sectors in the Aceh Province economy, so that commodities from which sectors are eligible for export at the national and international levels can be determined. By using secondary data, namely GDP and GRDP (gross regional domestic product) in 2017-2022. By using the Loation Quontient (LQ) analysis method. Shift Share (SS), and Klassen Typology. The results of the calculation of the three analyses in Aceh Province for 6 years, it can be identified from 17 economic sectors in Aceh Province there is 1 sector that is classified as a basic sector, namely the first sector of Agriculture, Forestry, and Fisheries. After that the researchers analyzed again with the same three analyses of the sub-sectors in the basic sector and found that of the seven sub-sectors in the basic sector, the plantation crop sub-sector was the basic sub-sector, then the researchers analyzed again the commodities in the sub-sector with the same three analyses so that it was found that of the 8 commodities, the Coffee commodity with an LQ value (3.96), Shift Share (5.7), Klassen Typology (quadrant 1), and the Cocoa commodity with an LQ value (2.24), Shift Share (13.8), Klassen Typology (quadrant 1). And from the results of the analysis that has been done, it can be concluded that commodities that have a great opportunity to be exported are Coffee commodities and Cocoa commodities.